The EuroPrevall birth cohort study on food allergy: baseline characteristics of 12,000 newborns and their families from nine European countries - McBride, D.; Keil, T.; Grabenhenrich, L.; Dubakiene, R.; Drasutiene, G.; Fiocchi, A.; Dahdah, L.; Sprikkelman, A. B.; Schoemaker, A. A.; Roberts, G.; Grimshaw, K.; Kowalski, M. L.; et al. (Pediatr Allergy Immunol, 2012)
It is unclear why some children develop food allergy. The EuroPrevall birth cohort was established to examine regional differences in the prevalence and risk factors of food allergy in European children using gold-standard diagnostic criteria. The aim of this report was to describe pre-, post-natal and environmental characteristics among the participating countries. In nine countries across four major European climatic regions, mothers and their newborns were enrolled from October 2005 through February 2010. Using standardized questionnaires, we assessed allergic diseases and self-reported food hypersensitivity of parents and siblings, nutrition during pregnancy, nutritional supplements, medications, mode of delivery, socio-demographic data and home environmental exposures. A total of 12,049 babies and their families were recruited. Self-reported adverse reactions to food ever were considerably more common in mothers from Germany (30%), Iceland, United Kingdom, and the Netherlands (all 20-22%) compared with those from Italy (11%), Lithuania, Greece, Poland, and Spain (all 5-8%). Prevalence estimates of parental asthma, allergic rhinitis and eczema were highest in north-west (Iceland, UK), followed by west (Germany, the Netherlands), south (Greece, Italy, Spain) and lowest in central and east Europe (Poland, Lithuania). Over 17% of Spanish and Greek children were exposed to tobacco smoke in utero compared with only 8-11% in other countries. Caesarean section rate was highest in Greece (44%) and lowest in Spain (<3%). We found country-specific differences in antibiotic use, pet ownership, type of flooring and baby's mattress. In the EuroPrevall birth cohort study, the largest study using gold-standard diagnostic criteria for food allergy in children worldwide, we found considerable country-specific baseline differences regarding a wide range of factors that are hypothesized to play a role in the development of food allergy including allergic family history, obstetrical practices, pre- and post-natal environmental exposures.
Keywords: Adult Allergens Cohort Studies Environmental Exposure Europe Family Female Food Hypersensitivity Humans Hypersensitivity Infant; Newborn Male Pregnancy Pregnancy Complications Prevalence Questionnaires Risk Factors